2011
DOI: 10.1371/journal.pcbi.1002085
|View full text |Cite
|
Sign up to set email alerts
|

Robust Network Topologies for Generating Switch-Like Cellular Responses

Abstract: Signaling networks that convert graded stimuli into binary, all-or-none cellular responses are critical in processes ranging from cell-cycle control to lineage commitment. To exhaustively enumerate topologies that exhibit this switch-like behavior, we simulated all possible two- and three-component networks on random parameter sets, and assessed the resulting response profiles for both steepness (ultrasensitivity) and extent of memory (bistability). Simulations were used to study purely enzymatic networks, pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
97
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(97 citation statements)
references
References 51 publications
(81 reference statements)
0
97
0
Order By: Relevance
“…For example, hundreds of distinct RNA sequences fold in the same secondary structure (3), as do proteins in their 3D structure (4). Similarly, distinct gene regulatory architectures can produce the same gene expression pattern (5,6) or temporal behavior (7,8). However, among these genotypes, some are more evolvable than others.…”
Section: Dynamics Of Gene Circuits Shapes Evolvabilitymentioning
confidence: 99%
“…For example, hundreds of distinct RNA sequences fold in the same secondary structure (3), as do proteins in their 3D structure (4). Similarly, distinct gene regulatory architectures can produce the same gene expression pattern (5,6) or temporal behavior (7,8). However, among these genotypes, some are more evolvable than others.…”
Section: Dynamics Of Gene Circuits Shapes Evolvabilitymentioning
confidence: 99%
“…A broad array of signaling strategies (e.g. positive feedback loops) have been proposed to underlie this robust ultrasensitivity response (Shah and Sarkar, 2011). Recent mathematical models (Ferrell, 1998;Bhalla, 2011;Santos et al, 2012;Harrington et al, 2013) have revealed that the subcellular spatial organization of signaling molecules is best suited for generating a diverse set of cellular states, including such bistable switches.…”
Section: Discussionmentioning
confidence: 99%
“…Our approach, however, is not biased towards any specific architecture since we evaluate the robustness of every possible three-component network. Similar studies have also been carried out, but for analyzing adaptation (Ma et al 2009), switch-like responses (Shah and Sarkar 2011) and patterning in response to morphogen gradients (Cotterell and Sharpe 2010).…”
Section: Introductionmentioning
confidence: 98%